Evaluation the Cytotoxic Effect of Lactobacillus Acidophilus Concentrated Filtrate on Growth of Tumor Cell Lines - Salih, Raja'a H (Al-Nahrain Journal of Science, 2012)
This study was designed to evaluate the cytotoxic effect of Lactobacillus acidophilus concentrated filtrate on growth of (AMN, REF, RD and HEPG2) tumor cell lines. The isolate obtained from vaginal swabs and identified according to culture characterictics and biochemical tests. Lb. acidophilus was grown in MRS broth media and incubated anaerobically for 24 hrs., then culture was centrifuged and sterilized by filtration. The filtrate was concentrated to three fold, then different concentrations (125, 250, 500 and 1000 μg/ml) were prepared and tested against the four types of tumor cell lines. Results showed that concentrated filtrate of Lb. acidophilus had a significant cytotoxic effect (P≤0.05) against the growth of tumor cells used in this study at the concentrations (125, 250 and 500 μg/ml) when compared with control and the concentration (125 μg/ml) had the highest effect against (AMN, REF, RD and HEPG2) tumor cell lines which showed growth inhibition percentages (90.40, 81.22, 90.37, 84.41)% respectively while the concentration (1000 μg/ml) displayed a significant effect on the HEPG2 cell line with growth inhibition percentage (35.78%).